Are there associations between sleep bruxism, chronic stress, and sleep quality? - Ohlmann, Brigitte; Bömicke, Wolfgang; Habibi, Yasamin; Rammelsberg, Peter; Schmitter, Marc (Journal of dentistry, 2018)
Objectives - The purpose of this study was to identify associations between definite sleep bruxism, as defined by the American academy of sleep medicine, and chronic stress and sleep quality. - Methods - Sleep bruxism was determined by use of questionnaires, assessment of clinical symptoms, and recording of electromyographic and electrocardiographic data (recorded by the Bruxoff® device). The study included 67 participants. Of these, 38 were identified as bruxers and 29 as non-bruxers. The 38 bruxers were further classified as 17 moderate and 21 intense bruxers. Self-reported stress and self-reported sleep quality were determined by use of the validated questionnaires “Trier Inventory for the Assessment of Chronic Stress” (TICS) and the “Pittsburgh Sleep Quality Index” (PSQI). - Results - No statistically significant association was found between sleep bruxism and self-reported stress or sleep quality. However, a significant association between specific items of chronic stress and poor sleep quality was identified. - Conclusions - The results of this study indicate an association between subjective sleep quality and subjective chronic stress, irrespective of the presence or absence of sleep bruxism. - Clinical significance - Chronic stress and sleep quality do not seem to be associated with sleep bruxism. (clinical trial no. NCT03039985)